2003
DOI: 10.2746/042516403776014217
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survey of laryngoplasty and ventriculocordectomy in an older, mixed‐breed population of 200 horses. Part 2: Owners' assessment of the value of surgery

Abstract: Summary Reasons for performing study: There is continuing debate on the clinical benefit of laryngoplasty (LP) in the treatment of equine laryngeal paralysis. In particular, there is little information available on the clinical value of this surgery in older horses, in non‐Thoroughbreds or in sports or pleasure horses; nor on the relationship between the degree of LP abduction achieved and the clinical value of LP. Objectives: To evaluate the owner's assessment of the value of LP(and combined ventriculocorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(96 citation statements)
references
References 17 publications
6
87
1
2
Order By: Relevance
“…Implant failure (by suture pull-out or prosthesis breakdown) has been reported in a small proportion (5%) of cases during the first week after surgery [21], and progressive loss of abduction may occur over time in many horses [21,[27][28][29][30]. A recent experimental study hypothesised that suboptimal post operative abduction may predispose horses to other forms of collapse due to increases in negative airway pressure, particularly in the regions of the right aryepiglottal fold and both vocal folds [31].…”
Section: Introductionmentioning
confidence: 99%
“…Implant failure (by suture pull-out or prosthesis breakdown) has been reported in a small proportion (5%) of cases during the first week after surgery [21], and progressive loss of abduction may occur over time in many horses [21,[27][28][29][30]. A recent experimental study hypothesised that suboptimal post operative abduction may predispose horses to other forms of collapse due to increases in negative airway pressure, particularly in the regions of the right aryepiglottal fold and both vocal folds [31].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical terms, 59% of horses were reported to have improved exercise performance after unilateral VEC compared to 75% of horses that underwent LP + VEC (Dixon et al . ; Taylor et al . ).…”
Section: Quantity and Quality Of Evidence Presentedmentioning
confidence: 97%
“…Other studies have found no effect of preoperative grade on the results of LP surgery (Dixon et al . ; Barakzai et al . ).…”
Section: Quantity and Quality Of Evidence Presentedmentioning
confidence: 97%
See 1 more Smart Citation
“…arış performansını olumsuz yönde etkileyen larengeal hemipleji, safkan ırklar başta olmak üzere bir çok yarış atı ırkında tanımlanmaktadır (1)(2)(3)(4).…”
Section: Introductionunclassified